World markets for raising new capital - Henderson, Brian J.; Jegadeesh, Narasimhan; Weisbach, Michael S. (Journal of Financial Economics, 2006)
We examine the extent to which firms from different countries rely on alternative sources of capital, the locations in which they raise capital, and the factors that affect these choices. During the 1990–2001 period, firms raised about 25.3 trillion of new capital, including 4.9 trillion from abroad. International debt issuances are substantially more common than equity issuances, with debt (equity) issues accounting for 87% (9%) of all securities issued internationally, and about 20% (12%) of all public debt issuances. Market timing considerations appear to be important in security issuance decisions in most countries.